Verbal Gestures in Cameroon - Pillion, Betsy; Grenoble, Lenore; Ngue Um, Emmanuel; Kopper, Sarah (My University, 2019)
This paper details the nature of a set of extra-grammatical units that we call verbal gestures, found in several communities in the Central, Littoral, and Southern regions of Cameroon. We lay out the verbal gestures found in these communities, explain their usage and distribution within the context of the community and the language of the user, and situate the system of verbal gestures found in Cameroon in the larger linguistic context of Cameroonian multilingualism. Furthermore, we make preliminary proposals for a system of sounds that exists outside of that of the primary phonemic system, which interacts with the system of verbal gestures.
Keywords: Cameroon; Verbal gestures; multilingualism; sounds